DIGITAL TRANSFORMATION, SHARIA GOVERNANCE, AND ORGANIZATIONAL PERFORMANCE IN ISLAMIC MICROFINANCE INSTITUTIONS - Nur Kholidah (PAPUA: International Journal of Sharia Business Management, 2026)
This study examines the relationship between digital transformation, Sharia governance, and organizational performance in Islamic Microfinance Institutions (IMFIs) within the context of achieving the objectives of maqasid al-shariah in the digital era. The research employs a qualitative approach using a literature review method based on secondary data collected from 30 scholarly articles and relevant institutional reports published between 2015 and 2025. The findings indicate that digital transformation plays a significant role in improving operational efficiency, expanding financial inclusion, enhancing customer services, and strengthening institutional competitiveness. Furthermore, effective Sharia governance ensures that technological innovation remains aligned with Islamic ethical principles, transparency, accountability, and compliance requirements. The integration of digital transformation and Sharia governance contributes positively to organizational performance by supporting financial sustainability, social impact, and stakeholder trust. The study also highlights that the implementation of digital technology within IMFIs can facilitate the achievement of maqasid al-shariah, particularly in the preservation of wealth, intellect, and social welfare. Therefore, a balanced integration of technological innovation and Islamic governance is essential for fostering sustainable development and long-term organizational success in Islamic microfinance institutions.